METHODOLOGY OF TEACHING POLITICAL SCIENCE: AN ANALYTICAL STUDY - Dey, Pradip (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Teaching methods are the way through which learning experiences or the messages are organized and sequenced and also different bits of learning experiences are integrated. There are several methods like lecture, discussion, question-answer, debate, seminar, project work, field work, computer- assisted learning, etc. These methods can be classified into three broad categories. These are teacher-controlled methods, learner-controlled methods and group-controlled methods. A classroom-learning environment is generally characterized by teacher, learner and their interaction through transaction of learning experiences with the help of appropriate methods and media. Different lessons or units demand different approaches of teaching. If a teacher uses the same methods or socialized recitation, it can be very monotonous indeed. A tremendous increase in equipment, materials, means and teaching procedures has been witnessed in the past few decades. It is necessary to be able to utilize all those to provide variety and colour to teaching political science. Today, with modem technology, a whole range of such devices are available which are commonly referred to as instructional aids or communication aids. Since these aids are presented through certain medium, these are also termed communication media. These aids supplement the methods used in curriculum transactions. In order to make the teaching-learning of political science effective, a teacher is required to be aware of the various methods of teaching political science. He should equip himself with the growth and development of technology, new teaching-learning resources so that he can use these in the process of teaching in need of the hour.